PENGARUH PEMUPUKAN TERHADAP PERTUMBUHAN BEBERAPA VARIETAS PADI GOGO (Oryza sativa L.) - Ade Alavan; Rita Hayati; Erita Hayati (Jurnal Floratek, 2015)
Effects of fertilization on growth of several varieties of upland rice have been studied.  The experiment was arranged in a randomized complete block design, 3 x 4 factorial design with three replications. Factors studied were fertilization i.e. 100% compost, 100% inorganic fertilizers, and mixture of 50% organic and inorganic fertilizers. Upland rice varieties consisted of Cirata, Limboto, Situ Bagendit, and Situ Patenggang. Results showed that mixture of 50% organic and inorganic was the best on plant height at  ages of 2, 3, 4, 5, 6, 7, 8 and 9 week after planting (WAP) and tiller numbers per hill. Meanwhile, 100% organic fertilizer was the best for flowering and harvesting ages. The best variety for plant height was Cirata and Situ Patenggang, while for tiller numbers was Situ Bagendit. There were interactions between fertilization and variety on plant height and tiller numbers.  The best combination for plant height was Situ Patenggang and mixture of 50% organic and inorganic, while for tiller numbers was Situ Bagendit and mixture of 50% organic and inorganic.